The Potential of Bandotan Leaves (Ageratum Conyzoides L.) Extract for Natural Curing of Eggs - Andi Novita (Jurnal Medika Veterinaria, 2014)
This study aims to determine the effect of eggs immersed in extracts of bandotan leaves on the organoleptic quality, haugh unit, and yolk index. The samples used were 105 eggs, weighing of 51.33 ± 55.9 grams collected from the farm in Jantho. By using a completely randomized design with factorialpattern the samples were divided into five treatment groups. P0 (control) was not given any treatment , P1 was immersed in 10 % bandotan leaf extract for12 hours, P2 was immersed in 10% bandotan leaf extract for 24 hours , P3 was immersed in 20% bandotan leaf extract for 12 hours and P4 wasimmersed in 20% bandotan leaf extract for 24 hours. The observation interval was done on week 0, 1, 2, 3, and 4. The organoloeptic observation of alleggs showed that either eggs on P1and P2 treatment showed no significant changes until week 4. The HU value of P0, P1, and P3 were 68.16 (grade A),70.34 (grade A), and 75.89 (grade AA), respectively. Yolk index value of P0, P1,and P2 were 0.65, 0.71, and 0.74 , respectively. In conclusion, the higherthe concentration of bandotan leaf extract given the longest the storage time of eggs based on the maintain of HU and YI value.____________________________________________________________________________________________________________________Key words: bandotan leaf, haugh unit, organoleptic, egg, yolk index